A method for detecting trace metal ions in PTFE resin
By using a mixture of alcohols and acidic pure water as the extractor and combined with shaker oscillation, the problem of low detection efficiency of trace metal ions in PTFE resin is solved, and the detection efficiency is significantly improved.
Patent Information
- Application Number
- CN202411855694.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The prior art is difficult to efficiently detect trace metal ions in PTFE resins, and due to the hydrophobicity of PTFE resins, it is difficult for traditional acidic solution immersion to fully contact the extract, resulting in low detection efficiency.
A mixed liquid composed of alcohols and acidic pure water is used as the extraction liquid, and combined with shaker oscillation, significantly improving the leaching efficiency of trace metal ions.
By optimizing the extraction conditions of the extracting solvent and shaker, the processing efficiency of samples before ICP-MS detection is significantly improved, and the detection efficiency of trace metal ions in PTFE resin is improved.
Smart Images

Figure CN119309887B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin detection, in particular to a method for detecting trace metal ions in PTFE resin. Background Art
[0002] PTFE material has strong chemical stability and is not easily corroded by acids, alkalis and other organic solvents. It is also resistant to low and high temperatures and can be used for a long time between -180℃ and 260℃. It also has excellent electrical insulation properties, which can effectively isolate the positive and negative poles of electronic components and prevent the occurrence of current short circuits and leakage. PTFE also has a low dielectric constant and dielectric loss, which can reduce energy loss and interference in signal transmission and improve the working efficiency and stability of electronic components. In addition, PTFE also has good anti-stickiness and lubricity. It is a high-performance polymer material and is therefore widely used in the semiconductor industry. In recent years, semiconductor manufacturing has required a high degree of purity in all industries. Impurity contamination introduced in each process may cause defects in semiconductor devices. Therefore, the purity of PTFE as a raw material is particularly important. Inductively coupled plasma mass spectrometry (ICP-MS) has played an important role in this regard.
[0003] At present, there are few reports on the precipitation of impurity elements in PTFE resin. Most of them are tests of impurity elements in PTFE products. However, in the process of product processing, there are bound to be problems such as pollution caused by processing equipment and powder transfer, and PTFE products can only test impurity elements on their surface. At the same time, the intermolecular force of PTFE resin is extremely low, and it has the characteristics of non-stickiness and strong hydrophobicity, which will make it difficult to fully contact the extraction solution when using acidic solution immersion test, and the surface immersion is incomplete. If it is immersed in organic solvents such as methanol, the ICP-MS matrix tube will turn black during sampling, the sampling cone will become dirty, and the sensitivity will decrease. Therefore, it is a challenge to detect metal ion precipitation of PTFE resin by immersion method.
[0004] Existing technologies such as Chinese patent document CN114397156A (application number 202111651239.1) disclose a sample pretreatment method for detecting trace metal ions in PTFE and its application. It also uses the ICP-MS detection method, but because its final solvent is still an acidic solvent, it takes a lot of time to pretreat the sample, such as constant temperature for 24 hours, standing for 4 hours, keeping warm for 3 hours, soaking for 7 days, etc., which seriously affects the detection efficiency of PTFE resin. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for detecting trace metal ions in PTFE resin. By optimizing the extraction solvent for trace metal ions and coordinating with shaking table oscillation, the processing efficiency of samples before ICP-MS detection is significantly improved, thereby greatly improving the detection efficiency of PTFE resin.
[0006] In order to achieve the above technical effects, the present invention uses the following technical solutions:
[0007] A method for detecting trace metal ions in PTFE resin comprises the following steps:
[0008] S1. Take the cleaned PTFE resin, disperse it in a mixture of alcohol organic matter and acidic pure water, seal it and put it into a shaker to extract the intermediate solution;
[0009] S2. The intermediate solution obtained in step S1 is centrifuged, and after standing for stratification, the supernatant is taken out, and the supernatant and the blank sample are respectively placed in a nitrogen blower and concentrated to dryness, and then acidic pure water is added to dissolve and dilute to obtain a sample solution to be tested;
[0010] S3. Prepare a standard solution of metal ions, establish a standard curve, and determine the concentration of metal ions in the sample solution using ICP-MS;
[0011] In step S1, the ratio of PTFE resin to the mixed solution is 1g: (10-20) mL;
[0012] In step S1, the volume ratio of alcohol and acidic pure water in the mixed solution is (2-4):1, the acidic pure water is prepared from nitric acid and ultrapure water, and the pH of the acidic pure water is 2.0;
[0013] In step S1, the conditions for the shaking extraction are 40°C-60°C, the rotation speed is 200rpm-300rpm, and the extraction time is 6h-8h;
[0014] In step S2, the blank sample is a mixed solution.
[0015] In the detection method provided by the present invention, a mixed solution composed of alcohols and acidic pure water is creatively used as the leaching solution of PTFE resin. Since the contact angle between PTFE resin and water is 138.1°, the hydrophobicity is strong, and the surface energy of the alcohol solution is similar to the surface energy of PTFE, the contact angle is significantly smaller than that of water (as shown in Table 1), and it has excellent wettability. This property allows the resin molecules to be effectively dispersed in the mixed solution, and also allows the acidic pure water in the leaching solution to enter the interior of the PTFE resin, so that the precipitation effect of trace metal ions is greatly improved, thereby solving the problem of poor precipitation effect of metal ions due to the hydrophobicity of PTFE resin. At the same time, the use of a shaking table for extraction also greatly shortens the overall extraction time and further improves the pre-treatment efficiency.
[0016] Table 1 Contact angle
[0017]
[0018] Preferably, in step S1, the PTFE resin is in powder form. The powdered PTFE resin has a larger contact area with the extracting solution, which is more conducive to the extraction of metal ions.
[0019] Preferably, in step S1, the alcohol organic compound is selected from one of methanol, ethanol and isopropanol.
[0020] Preferably, in step S1, the cleaning process of the PTFE resin is to use ultrapure water to continuously clean the PTFE resin for more than 5 times, and the duration of each cleaning is ≥ 2 minutes.
[0021] Preferably, in step S1, the nitric acid used to prepare the acidic pure water is electronic grade, and the mass concentration of the nitric acid is 60wt%; and the resistivity of the ultrapure water used to prepare the acidic pure water is ≥18.2MΩ·cm.
[0022] Preferably, in step S2, the centrifugal speed is 7000 rpm-10000 rpm, and the centrifugal time is 15 min-20 min.
[0023] Preferably, in step S2, the heating temperature in the nitrogen blowdown apparatus is 70°C-85°C, and the gas flow rate is (0.5-0.7) mL / min.
[0024] In the detection method provided by the present invention, the methanol solution is removed by using a nitrogen blower and then dissolved and diluted with an acidic pure water solution to prepare a sample solution to be tested, thereby effectively avoiding problems such as damage to the ICP-MS instrument matrix tube and decreased sensitivity caused by directly using the methanol solution for sampling.
[0025] Preferably, in step S3, the concentrations of the metal ion standard solutions are 0 ppb, 10 ppb, 20 ppb, 50 ppb and 100 ppb, respectively, and the metal ion standard solutions contain 45 Sc, 103 Rh, 115 In, 209 Mixed standard solution of Bi.
[0026] Preferably, when using ICP-MS to measure the concentration, the online addition of internal standard method and collision reaction cell can effectively remove some background interference in the air and sample matrix, optimize the instrument performance conditions, make the linear correlation coefficient of the measured curve reach above 0.999, the method detection limit of metal ions is 0.001-0.08ppb, and RSD≤5%. It has the advantages of high sensitivity, good repeatability, high accuracy, etc.
[0027] Preferably, all containers in the detection method are made of PFA material.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. PTFE resin has a strong hydrophobic property. The detection method provided by the present invention cleverly utilizes the property that the surface energy of alcohol solution is similar to the surface energy of PTFE. The contact angle of alcohol solution is small enough to make the alcohol solution wet the PTFE resin, so that the resin molecules can be dispersed in the alcohol, and acidic pure water can also enter the interior of the PTFE resin to increase the metal ion precipitation effect, thereby solving the problem that the PTFE resin cannot be well infiltrated and precipitated due to its hydrophobic property.
[0030] 2. The detection method provided by the present invention greatly improves the pre-treatment efficiency, and the metal ion extraction effect in the sample is significant and more accurate; by performing multiple extraction experiments on the same batch of samples, the experimental results are almost the same and have high reproducibility, which provides favorable conditions for accurately judging the content of metal ions in the sample. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : The standard curve diagram of element Al provided in Example 1;
[0032] Figure 2 : The standard curve diagram of element Ba provided in Example 1;
[0033] Figure 3 : The standard curve diagram of element Ca provided in Example 1;
[0034] Figure 4 : The standard curve diagram of the element Cu provided in Example 1;
[0035] Figure 5 : The standard curve diagram of the element Fe provided in Example 1;
[0036] Figure 6 : The standard curve diagram of element Mg provided in Example 1;
[0037] Figure 7 : The standard curve diagram of the element Mn provided in Example 1;
[0038] Figure 8 : The standard curve diagram of element Na provided in Example 1;
[0039] Fig. 9 : Standard curve diagram of element Zn provided in Example 1. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0041] The reagents and devices used in the examples and comparative examples are all commercially available reagents and devices in the art, such as:
[0042] Nitric acid was purchased from Merck;
[0043] Methanol was purchased from Merck;
[0044] Ultrapure water was purified by the Milli-Q Element A10 system;
[0045] Mixed standard solutions (aluminum, barium, calcium, copper, iron, magnesium, manganese, sodium, zinc) and mixed internal standard solutions (scandium, rhodium, indium, bismuth) were purchased from SGS;
[0046] Mass spectrometry tuning liquid: ultrapure water: ≥98.5%; nitric acid: <1.5%; Be: 1ppm; Bi: 200ppb; In: 200ppb; Ce: 200ppb; Co: 500ppb; Mn: 500ppb, purchased from Shimadzu;
[0047] The specific sources of other reagents and equipment are not described here.
[0048] The instrument conditions were optimized using 2 ppb tuning solution. The optimized parameters are shown in Table 2:
[0049] Table 2 Instrument conditions
[0050]
[0051] The instrument conditions shown in Table 1 were used in each embodiment and comparative example.
[0052] Example 1
[0053] A method for detecting trace metal ions in PTFE resin.
[0054] In this embodiment, three types of PTFE suspension resins are used, namely sample A, sample B and sample C.
[0055] The detection method specifically includes the following steps:
[0056] S1. Cleaning PTFE resin: weigh 1 g of PTFE resin for each sample, clean the PTFE resin with ultrapure water for 6 times, each cleaning time is 3 min, and then blow dry with high-purity nitrogen;
[0057] Preparation of a mixed solution: Methanol and acidic pure water are mixed in a volume ratio of 2:1 to prepare a mixed solution, wherein the acidic pure water is prepared from nitric acid and ultrapure water, the pH of the acidic pure water is 2.0, the nitric acid used to prepare the acidic pure water is electronic grade, and the mass concentration of the nitric acid is 60wt%; the resistivity of the ultrapure water used to prepare the acidic pure water is 18.2MΩ·cm;
[0058] The cleaned PTFE resin was dispersed in 10 mL of the mixed solution in the PFA tube, and the PFA tube was sealed and placed in a shaker with the parameters set at 50°C, 250 rpm, and 6 h to extract the metal ions and obtain an intermediate solution;
[0059] S2. The intermediate solution obtained in step S1 was transferred to a centrifuge tube made of PFA material, placed in a centrifuge, and the parameters were set to 7000rpm, 20min, and the supernatant was taken out after standing and stratification after centrifugation, and 10mL of the mixed solution was taken as a blank sample. The supernatant and the blank sample after centrifugation were placed in a nitrogen blower, concentrated to dryness at a temperature of 85°C and a gas flow rate of 0.7mL / min, and 5mL of acidic pure water was added to dissolve and dilute to the sample solution to be tested;
[0060] S3. Prepare metal ion standard solution: take 0, 100 μL, 200 μL, 500 μL and 1000 μL of 10 ppm mixed standard solution respectively, place them in five 100 mL volumetric flasks, dilute to volume with ultrapure water, that is, prepare standard solutions containing the elements to be tested with concentrations of 0 ppb, 10 ppb, 20 ppb, 50 ppb and 100 ppb, then take 50 μL of the internal standard solution with a concentration of 10 ppm and place it in a 100 mL volumetric flask, dilute to volume with ultrapure water, that is, prepare an internal standard solution of 5 ppb,
[0061] To establish a standard curve, Figure 1-Figure 9 As shown, the linear correlation coefficients of the standard curves were all above 0.999;
[0062] The standard mode combined with the collision reaction cell method and the online internal standard addition method are used to quantitatively measure the solution to be tested by ICP-MS. According to the measured intensity of the sample to be tested, the standard curve is converted to obtain the test result of the metal ion content in the solution. Then the mass conversion is performed, that is, the ion precipitation concentration in the sample (μg / kg) = ;
[0063] Where: C1 is the concentration of the test sample (μg / L); C0 is the concentration of the blank sample (μg / L); V is the volume of the sample to be tested after dilution and concentration (L); M is the mass of the extracted sample (kg).
[0064] The test results are shown in Table 3.
[0065] Table 3 Test results of Example 1
[0066]
[0067] Furthermore, the spiked recovery rate was adopted to verify the accuracy of this method. Specifically, a certain amount of standard solution was added to the sample, and the spiked recovery rate was measured; wherein, spiked recovery rate = (measured value - blank value / added value) × 100%. The spiked recovery rate and method detection limit of this detection method are shown in Table 4. As shown in Table 4, the spiked recovery rate of this method is 83.6%-105%, indicating that this method is not easy to cause element loss and has high accuracy; the method detection limits of each metal element in this method are all in the range of 0.001-0.08 ppb, indicating that this method has high sensitivity.
[0068]
[0069] Example 2
[0070] The only difference between this embodiment and embodiment 1 is that the volume ratio of methanol and acidic pure water in the mixed solution is 3:1; the ratio of PTFE resin to methanol solution is 1 g:10 mL; the setting parameters of the shaker are 50°C, 250 rpm and 8 h; the setting parameters of the centrifuge are 7000 rpm and 20 min; and the setting parameters of the nitrogen blowdown instrument are 85°C and a gas flow rate of 0.7 mL / min.
[0071] The other steps are the same as those in Implementation Example 1 and will not be repeated here.
[0072] The analysis results of the samples in this example are shown in Table 5.
[0073] Table 5 Test results of Example 2
[0074]
[0075] Example 3
[0076] The only difference between this embodiment and embodiment 1 is that the mixed solution consists of acidic pure water and isopropanol, and the ratio of isopropanol to acidic pure water is 4:1; the ratio of PTFE to alcohol solution is 1 g:10 mL; the setting parameters of the shaker are 50°C, 250 rpm and 6 h; the setting parameters of the centrifuge are 7000 rpm and 20 min; the setting parameters of the nitrogen blowdown instrument are 85°C and a gas flow rate of 0.7 mL / min.
[0077] The other steps are the same as those in Implementation Example 1 and will not be repeated here.
[0078] The analysis results of the samples in this example are shown in Table 6.
[0079] Table 6 Test results of Example 3
[0080]
[0081] Example 4
[0082] The only difference between this embodiment and embodiment 1 is that only 1 g of PTFE resin of sample A is weighed and 7 groups of parallel samples are set.
[0083] The other steps are the same as those in Implementation Example 1 and will not be repeated here.
[0084] The analysis results of the samples in this example are shown in Table 7.
[0085] Table 7 Test results of Example 4
[0086]
[0087] As shown in Table 7, the relative standard deviations of all elements were less than 5% when the same sample was extracted multiple times, indicating that the method has good reproducibility.
[0088] Comparative Example 1
[0089] The only difference between this comparative example and Example 1 is that the ratio of methanol to acidic pure water in the mixed solution is 1:1. The other steps are the same as those in Example 1 and will not be repeated here.
[0090] The analysis results of the samples of this comparative example are shown in Table 8.
[0091] Table 8 Test results of comparative example 1
[0092]
[0093] Comparative Example 2
[0094] The difference between this comparative example and Example 1 is that no methanol solution is prepared during extraction, and the PTFE resin is directly soaked in acidic pure water; no nitrogen blowdown instrument is used for concentration, and the extract after centrifugation is directly tested.
[0095] The other steps are the same as those in Implementation Example 1 and will not be repeated here.
[0096] The analysis results of the samples of this comparative example are shown in Table 9.
[0097] Table 9 Test results of comparative example 2
[0098]
[0099] Comparative Example 3
[0100] The only difference between this comparative example and Example 1 is that when the alcohol solution is used for extraction, the setting parameters of the shaking table are 25° C., 200 rpm, and 2 h.
[0101] The other steps are the same as those in Implementation Example 1 and will not be repeated here.
[0102] The analysis results of the samples of this comparative example are shown in Table 10.
[0103]
[0104] Comparative Example 4
[0105] The only difference between this comparative example and Example 1 is that no shaking table is used, and the sample soaked in the methanol solution with a ratio of 2:1 is left for 24 hours.
[0106] The other steps are the same as those in Implementation Example 1 and will not be repeated here.
[0107] The analysis results of the samples of this comparative example are shown in Table 11.
[0108] Table 11 Test results of comparative example 4
[0109]
[0110] From the above data results, it can be seen that as the concentration of alcohol in the mixed solution becomes higher and higher, the improvement rate of the infiltration and extraction effect gradually tends to be stable. When the ratio of alcohol to acidic pure water is 2:1, the infiltration and extraction effect is relatively good and the amount of alcohol used is the least. This ratio is the most economical ratio. At the same time, as the shaking time increases, the infiltration and extraction effect of each metal element gradually tends to be stable. When the shaking time is more than 6 hours, the infiltration and extraction effect is best, and the test results are more stable after using the shaker, and the relative standard deviation is lower.
Claims
1. A method for detecting trace metal ions in PTFE resin, characterized in that: The steps include: S1. Take the cleaned PTFE resin, disperse it in a mixture of alcohol organic matter and acidic pure water, seal it and put it into a shaker to extract the intermediate solution; S2. The intermediate solution obtained in step S1 is centrifuged, and after standing for stratification, the supernatant is taken out, and the supernatant and the blank sample are respectively placed in a nitrogen blower and concentrated to dryness, and then acidic pure water is added to dissolve and dilute to obtain a sample solution to be tested; S3. Prepare a standard solution of metal ions, establish a standard curve, and determine the concentration of metal ions in the sample solution using ICP-MS; In step S1, the ratio of PTFE resin to the mixed solution is 1g: (10-20) mL; In step S1, the volume ratio of alcohol and acidic pure water in the mixed solution is (2-4):1, the acidic pure water is prepared from nitric acid and ultrapure water, the pH of the acidic pure water is 2.0, and the alcohol organic matter is selected from one of methanol, ethanol or isopropanol; In step S1, the conditions for the shaking extraction are 40°C-60°C, the rotation speed is 200rpm-300rpm, and the extraction time is 6h-8h; In step S2, the blank sample is a mixed solution; In step S1, the PTFE resin is in powder form; In step S1, the alcohol organic matter effectively disperses the PTFE resin in the mixed solution, and the acidic pure water enters the interior of the PTFE resin to improve the metal ion precipitation effect.
2. The method for detecting trace metal ions in PTFE resin according to claim 1, wherein: In step S1, the cleaning process of the PTFE resin is to use ultrapure water to continuously clean the PTFE resin for more than 5 times, and the duration of each cleaning is ≥ 2 minutes.
3. The method for detecting trace metal ions in PTFE resin as claimed in claim 1, characterized in that In step S1, the nitric acid used to prepare the acidic pure water is electronic grade, and the mass concentration of the nitric acid is 60wt%; the resistivity of the ultrapure water used to prepare the acidic pure water is ≥18.2MΩ·cm.
4. The method for detecting trace metal ions in PTFE resin according to claim 1, wherein: In step S2, the centrifugal speed is 7000 rpm-10000 rpm, and the centrifugal time is 15 min-20 min.
5. The method for detecting trace metal ions in PTFE resin according to claim 1, wherein: In step S2, the heating temperature in the nitrogen blowdown apparatus is 70°C-85°C, and the gas flow rate is (0.5-0.7) mL / min.
6. The method for detecting trace metal ions in PTFE resin according to claim 1, wherein: In step S3, the concentrations of the metal ion standard solutions are 0 ppb, 10 ppb, 20 ppb, 50 ppb and 100 ppb respectively. 45 Sc, 103 Rh, 115 In, 209 Mixed standard solution of Bi.
7. The method for detecting trace metal ions in PTFE resin according to claim 1, wherein: When ICP-MS was used to determine the concentration, the online internal standard addition method and collision reaction cell were used, and the linear correlation coefficient of the measured curve reached above 0.
999. The method detection limit of metal ions was 0.001-0.08ppb, and RSD≤5%.
8. The method for detecting trace metal ions in PTFE resin according to claim 1, wherein: All containers in the detection method are made of PFA material.
Citation Information
Patent Citations
Sample pretreatment method for detecting trace metal ions in PTFE and application of sample pretreatment method
CN114397156A
Analysis method of trace of metal
JP2008203032A